The Importance of the Koala in Aboriginal Society in Nineteenth-Century Queensland (Australia): A Reconsideration of the Archival Record. (2nd January 2022) - Cahir, Fred; Schlagloth, Rolf; Clark, Ian D.
ABSTRACT: The principal purpose of this study was to gain a greater understanding of the utilitarian and symbolic significance of koalas for Aboriginal communities in Queensland, Australia as recorded by colonists during the early period of colonization and the early twentieth century. It does this primarily through a close examination of the nineteenth-century and early twentieth-century archival records and contemporary publications that relate to Queensland Aboriginal peoples' associations with koalas. This paper is the third in a series investigating the historic and cultural importance of the koala according to the location in Australia. It likewise employs the historical method approach, which relies on identifying historical sources, evaluating their relative authority, and combining their testimony appropriately in order to construct an accurate and reliable picture of past events and environments. Through a critique of the published historical sources, the distribution of and the etymology of "koala" are briefly discussed before an examination is made of the animal's spiritual importance, associated cultural traditions, and simultaneous utilitarian role. Mirroring previous studies published by the authors on Victoria and New South Wales, we confirm that the predominately non-Aboriginal historical records reveal that koalas were hunted for food and their skin in some Queensland regions. It shall be seen that the ethno-historical records are inconclusive about the koala's distribution in Queensland, whether they were hunted across all of the state at the point of colonization and whether they were considered an integral food source in some regions. Furthermore, this study demonstrates that the extent to which they were used varied across regions and between language groups and was subject to certain rules, and that their spiritual significance can be traced directly to epic creation stories. The implications of this paper are consistent with the earlier New South Wales and Victorian studies: regional variations exist in Queensland in relation to the (pre-colonial, colonial and post-colonial) historic relationship between Aboriginal communities and koalas and that close consultation with Aboriginal communities needs to be taken into consideration when planning conservation measures relating to koalas.